Estudo clinico da efetividade entre duas doses de dexametasona (4mg e 12mg) no controle da dor,edema e trismo após a cirurgia de terceiros molares inferiores inclusos - Agostinho, Cícero Newton Lemos Felício (2011)
The aim of this study was to evaluate the effect of two different concentrations (4 mg and 12 mg) of dexamethasone to control pain, swelling and trismus after third molar surgery inclusos. This clinical study was conducted with 16 adult patients of both sex, displaying mandibular third molar in the same position bilaterally, with an indication for surgical removal. Patients were treated with 4 mg or 12 mg of dexamethasone 1 hour before surgery on the first or second surgery. The choice of which side was operated first and which dose of dexamethasone would be taken first was performed randomly and double blind. The trismus was assessed by measuring the distance interincisal. Pain was assessed by the amount of tablets (paracetamol 750mg) taken after the surgery and the visual analogue pain scale (VAS). These data were obtained before surgery, 24 and 48 hours after surgery. Based on statistical analysis (Student's t test, Wilcoxon and Friedman), the results showed no differences in variables (swelling, pain and trismus) between the two doses of dexamethasone (4mg and 12mg).